THE IMPORTANCE OF ASSESSING QUALITY OF LIFE IN PATIENTS WITH NON-COMMUNICABLE DISEASES - Rasulova Nilufar Farxadovna; Mukhamedova Nigora Saydimuxtarovna (Journal Park Publishing, 2025)
Non-communicable diseases are a leading cause of long-term morbidity and disability worldwide, significantly influencing patients’ physical, psychological, and social well-being. In recent years, the assessment of quality of life has become an essential component of comprehensive healthcare evaluation, complementing traditional clinical and laboratory indicators. Quality of life reflects the patient’s subjective perception of health status, functional capacity, emotional stability, and social participation. This article emphasizes the importance of studying and assessing quality of life in patients with non-communicable diseases, highlighting its role in patient-centered care, treatment effectiveness evaluation, and long-term disease management. Systematic quality of life assessment enables healthcare professionals to better understand disease burden, optimize therapeutic strategies, and improve overall health outcomes.
Keywords: Non-communicable diseases, quality of life assessment, chronic disease, patient-centered care, health outcomes.